Antibody Response to Hepatitis B Virus Vaccine is Impaired in Patients With Inflammatory Bowel Disease on Infliximab Therapy. Issue 2 (18th January 2018) - Pratt, Perry K; David, Nunes; Weber, Horst C; Little, Frédéric F; Kourkoumpetis, Themistoklis; Patts, Gregory J; Weinberg, Janice; Farraye, Francis A
Abstract: Background: Studies have demonstrated an association between anti-TNF/immunomodulator agents used in inflammatory bowel disease (IBD) and impaired hepatitis B virus (HBV) vaccine immunogenicity, but little data exist on whether specific medication types affect protective HBsAb titers. Our aim was to analyze this association. Methods: This is a retrospective cohort study. Inclusion criteria: age ≥18, diagnosis of Crohn's disease (CD) or ulcerative colitis (UC), previous HBV vaccination series and/or ≥1 positive HBsAb, and record of IBD therapy in 6 months before titer level. Patients were stratified based upon medication exposures: anti-TNF, immunomodulator, combination anti-TNF and immunomodulatory, and a reference arm. Titer levels following vaccination and specific medication types given in the 6 months before titer were recorded. Seroprotection was defined as HBsAb ≥10 IU/ l and ≥100 IU/ l . Results: The study cohort (N = 391) was 70.8% white, 51.4% female and 64.2% had CD and 35.8% had UC. The mean age was 45.8 years. A significantly lower percentage of patients exposed to anti-TNF, immunomodulator or dual therapy had titers ≥10 ( P < 0.01). Regarding specific medications, only patients exposed to infliximab ( P < 0.01) were less likely to have titer levels ≥10, after controlling for other medication exposures, age at titer level, and interval time between vaccination/titer level. This was not found for patients exposed to adalimumab, methotrexate, 6-mercaptopurine, or azathioprine. Conclusions: Patients exposed to infliximab were significantly less likely to have protective HBsAb titer levels following vaccination, a trend not seen in patients on adalimumab. Efforts to vaccinate IBD patients against HBV before use of immunomodulators and anti-TNFs, infliximab specifically, and screen periodically thereafter must be reinforced.